Menemukan Jati Diri Bangsa Melalui Bahasa Indonesia - Widada, Dwi Masdi (J-PIPS (Jurnal Pendidikan Ilmu Pengetahuan Sosial), 2016)
The Indonesian people known to the world as the diverse peoples and tribes. A nation that has a diversity of cultures, especially languages. Language and culture in the archipelago together to get to know each other through Indonesian. The process of the journey is not as easy to reverse the hands. Through the youth who live in his time, the historical milestone of the nation begins. Indonesian introduced Youth Pledge October 28, 1928 is a major milestone for the Indonesian nation. Indonesian is not just a communication tool between the speaker and the listener. Indonesian not just lessons are only given in schools. Indonesian is a means of unifying the diversity of cultures, customs, and ethnicities in the country. Literature as a bridge for the reader to know the culture presented through the language. Indoneisa language becomes a medium of communication culture through literature. The students have not been able to understand the significance of a language sebagaai means of unifying values of the culture, customs, and ethnicities. The students looked at, Indonesian merely subjects to be solved in the classroom with no follow-up in everyday life. Literature must be taught to the students in order daa developing creativity and imagination of children. Language development is increasingly fast. This development should be followed with the spirit and sense of belonging of a language. It is not yet visible to students today. The deciding factor is how many speakers Indonesian Indonesian menggunkan in everyday life. How many students we know the world of literature. Lesson literature becomes desirable, but inside it contains the values of life that is very useful for future generations. Language is a reflection of the nation as an identity that would distinguish with other nationsKeywords: Nation, Culture, and Language